Petrography, mineral chemistry and provenance of basement clasts in the CRP-1 drillcore (Victoria Land Basin, Antarctica) - TALARICO, F.; SANDRONI, S. (1998)
Petrographical and mineral chemistry data are described for the most representative basement lithologies occurring as clasts (pebble grain-size class) from the CRP-1 drillcore. Most pebbles consist of either undeformed or foliated biotite with or without hornblende monzogranites. Other rock types include biotite with or without garnet syenogranite, biotite-hornblende granodiorite, tonalite, monzogranitic porphyries, haplogranite, quartz-monzonite (restricted to the Quaternary section), Ca-silicate rocks and biotite amphibolite (restricted to the Miocene strata). The common and ubiquitous occurrence of biotite with or without hornblende monzogranite pebbles, in both the Quaternary and Miocene sections, apparently mirrors the dominance of these rock types in the granitoid assemblages which are presently exposed in the upper Precambrian- lower Palaeozoic basement of south Victoria Land. The other CRP-1 pebble lithologies show petrographical features which consistently support a dominant supply from areas of the Transantarctic Mountains located to the west and south-west of the CRP-1 site, and they thus further corroborate a model of local provenance for the supply of basement clasts to the CRP-1 sedimentary strata.